HUBUNGAN PERSEPSI KELUARGA TENTANG WAKTU KUNJUNGAN DENGAN DUKUNGAN KELUARGA DALAM PEMENUHAN KEBUTUHAN SPIRITUAL PASIEN DI RUANG ICU - Fauziana Dzulhia Putri (2022)
Background: The importance of family presence for patients in the intensive care unit in the healing process. However, due to the policy of limiting visiting hours, the family cannot always be beside the patient and hinders the approach process between the patient and family. Purpose: This study aims to determine the relationship between family perceptions of visit time with family support in meeting the spiritual needs of patients in the ICU. Methods: This study used a Correlation Study research design with a cross-sectional approach. Results: The results of this study indicate that the patient's family in the ICU Respondents are mostly aged 21-30 years, namely 21 respondents (43.8%), female sex as many as 26 respondents (54.2%), and high school education as many as 29 respondents (60 respondents). ,4%). The results of bivariate analysis using the chi square test with the results showed p value 0.331 > 0.05. This shows that there is no significant relationship between the family's perception of the time of visit with family support in meeting the spiritual needs of patients in the ICU.